Triage and Evacuation of High-Risk Pilgrims at Surabaya Debarkation in 2024: Case Report - novia, annisa; Griana, Tias Pramesti (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 2 (2024): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2024)
Triage activity is a fundamental function in emergency departments (EDs), who are many patients may come at the same time. The purpose of the triage system is to ensure that patients will be treated according to their clinical urgency, which refers to the time critical interventions. Primary triage or field triage usually use simple triage techniques and rapid treatment that relies on rapid assessment of respiratory status, perfusion, bleeding control, and mental status. In these cases, it is still not in line with the rules for triage, which classification prioritizes patients with wheelchairs who need immediate treatment to be evacuated first. To overcome is these challenges, the solution that can be provided is coordination between the airline and the Indonesian Hajj Health team, to be able to ensure pilgrims get immediate treatment, so that they can be quickly evacuated. Handling of patients with the red category have to done immediately and patients with the green category who use wheelchairs will treat after that. In debarkation field triage applied as primary triage with a purpose to determine priority of treatment at the scene and to transport patients to the hospital immediately. So that the role of the process on mobilizing pilgrims with wheelchairs from the plane to the bus can be improved by referring to the triage process.